Academic emotions, college adjustment, and dropout intention in university students - Cobo-Rendón, Rubia; Hojman, Viviana; García-Álvarez, Diego; Cobo Rendon, Ramon (Frontiers in Education, 2023)
In recent years, due to the COVID-19 pandemic, the entrance and development of university life has become a complex process, making it relevant to investigate which variables could facilitate the adaptation of young people to university. This study aimed to analyze academic emotions and their prediction of university adaptation and intention to drop out. The study was quantitative, explanatory, and cross-sectional. A 295 university student from the Psychology program participated. Academic emotions were assessed with the short version of The Achievement Emotions Questionnaire, adaptation to university life with the reduced version of the Student Adjustment to College Questionnaire, and intention to drop out with three items designed to measure this variable. Results: Differences were identified in the emotions experienced during classes and study by students according to the year of entry. We found that males report experiencing emotions such as enjoyment and hope more during evaluations. Generally, students report positive emotions in their academic experience. Positive emotions predict adaptation to university life and the intention to study.